Effects of aging on cerebral blood flow, oxygen metabolism, and blood oxygenation level dependent responses to visual stimulation - Ances, Beau M.; Liang, Christine L.; Leontiev, Oleg; Perthen, Joanna E.; Fleisher, Adam S.; Lansing, Amy E.; Buxton, Richard B. (Human brain mapping, 2009)
Calibrated functional magnetic resonance imaging (fMRI) provides a noninvasive technique to assess functional metabolic changes associated with normal aging. We simultaneously measured both the magnitude of the blood oxygenation level dependent (BOLD) and cerebral blood flow (CBF) responses in the visual cortex for separate conditions of mild hypercapnia (5% CO2) and a simple checkerboard stimulus in healthy younger (n = 10, mean: 28‐years‐old) and older (n = 10, mean: 53‐years‐old) adults. From these data we derived baseline CBF, the BOLD scaling parameter M, the fractional change in the cerebral metabolic rate of oxygen consumption (CMRO2) with activation, and the coupling ratio n of the fractional changes in CBF and CMRO2. For the functional activation paradigm, the magnitude of the BOLD response was significantly lower for the older group (0.57 ± 0.07%) compared to the younger group (0.95 ± 0.14%), despite the finding that the fractional CBF and CMRO2 changes were similar for both groups. The weaker BOLD response for the older group was due to a reduction in the parameter M, which was significantly lower for older (4.6 ± 0.4%) than younger subjects (6.5 ± 0.8%), most likely reflecting a reduction in baseline CBF for older (41.7 ± 4.8 mL/100 mL/min) compared to younger (59.6 ± 9.1 mL/100 mL/min) subjects. In addition to these primary responses, for both groups the BOLD response exhibited a post‐stimulus undershoot with no significant difference in this magnitude. However, the post‐undershoot period of the CBF response was significantly greater for older compared to younger subjects. We conclude that when comparing two populations, the BOLD response can provide misleading reflections of underlying physiological changes. A calibrated approach provides a more quantitative reflection of underlying metabolic changes than the BOLD response alone. Hum Brain Mapp 2009. © 2008 Wiley‐Liss, Inc.